The gut microbiota and endometriosis: From pathogenesis to diagnosis and treatment - Qin, Rui; Tian, Gengren; Liu, Junbao; Cao, Lu (Frontiers in Cellular and Infection Microbiology, 2022)
Endometriosis is a common gynecological disease, that often leads to pain and infertility. At present, the specific pathogenesis of endometriosis has not been clarified, but it may be closely related to an imbalance of sex hormones in the body, ectopic hyperplasia stimulated by immune inflammation, and invasion and escape based on tumor characteristics. Gut microbiota is associated with many inflammatory diseases. With the further study of the gut microbiota, people are paying increasing attention to its relationship with endometriosis. Studies have shown that there is an association between the gut microbiota and endometriosis. The specific ways and mechanisms by which the gut microbiota participates in endometriosis may involve estrogen, immune inflammation, and tumor characteristics, among others. Therefore, in the future, regulating gut microbiota disorders in various ways can help in the treatment of endometriosis patients. This study reviewed the research on the gut microbiota and endometriosis in order to provide ideas for clinical diagnosis and treatment.